THC exposure during adolescence increases impulsivity-like behavior in adulthood in a WIN 55,212-2 self-administration mouse model - Cajiao-Manrique, María del Mar; Casadó-Anguera, Verònica; García-Blanco, Alejandra; Maldonado, Rafael; Martín-García, Elena (Frontiers in Psychiatry, 2023)
Cannabis addiction is a chronically relapsing disorder lacking effective treatment. Regular cannabis consumption typically begins during adolescence, and this early cannabinoid exposure may increase the risk for drug addiction in adulthood. This study investigates the development of cannabis addiction-like behavior in adult mice after adolescent exposure to the main psychoactive component of cannabis, Δ9-tetrahydrocannabinol (THC). Adolescent male mice were exposed to 5 mg/kg of THC from postnatal days 37 to 57. Operant self-administration sessions of WIN 55,212-2 (12.5 μg/kg/infusion) were conducted for 10 days. Mice were tested for three addiction-like criteria (persistence of response, motivation, and compulsivity), two parameters related with craving (resistance to extinction and drug-seeking behavior), and two phenotypic vulnerability traits related to substance use disorders (impulsivity and reward sensitivity). Additionally, qPCRs assays were performed to detect differentially expressed genes in medial prefrontal cortex (mPFC), nucleus accumbens (NAc), dorsal striatum and hippocampus (HPC) of “addicted” and “non-addicted” mice. Adolescent THC exposure did not modify WIN 55,212-2 reinforcement nor the development of cannabis addiction-like behavior. Inversely, THC pre-exposed mice displayed impulsive-like behavior in adulthood, which was more pronounced in the subgroup of mice that developed the addiction-like criteria. Moreover, downregulated drd2 and adora2a gene expression in NAc and HPC was revealed in THC pre-exposed mice, as well as a downregulation of drd2 expression in mPFC of vehicle pre-treated mice that developed addiction-like behaviors. These findings suggest that adolescent THC exposure may promote impulsivity-like behavior in adulthood, associated with downregulated drd2 and adora2a expression in NAc and HPC.